Healer-mental health personal decision aid / Huda Nabila Ishak and Norfiza Ibrahim - Ishak, Huda Nabila; Ibrahim, Norfiza (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Healer is an application whose goal is to help adults recognise their mental health problems and control the symptoms. The goal of this project is to develop a personal aid for adults who are struggling with mental health problems. A design science research methodology (DSRM) was used to develop and evaluate materials to help address the identified problems. During the evaluation, the benchmark scale was measured, analysed, and recorded. The results demonstrate that the attractiveness scale is above average, the perspicuity scale is excellent, the efficiency scale is good, the stimulation scale is above average, the dependability scale is above average, but the novelty is bad. The design and development of the Healer achieved all of the objectives of this study, including outlining the requirements and techniques for developing a mobile mental health application.